Analysis of Heavy Metal Content in Fried Foods Wrapped in Black Plastic as a Fried Food Wrap - Fathor Rahman; Nia Sari; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Fried foods or weci are also called Ote-ote. Ote-ote is a type of fried food which is usually more wrapped in black plastic, where the plastic contains the presence of heavy metal Pb. So this study aims to analyze the effect of heavy metal content (Pb) using new cooking oil and used cooking oil on fried food processing with a hot temperature of 80 0C, moderate temperature of 45 0C, and cold temperature of 25 0C with a 10 minute wrapping time. This study uses a Randomized Block Design (RBD) method, the sampling technique is carried out by Random Sampling with a sample of 30 consisting of fried foods and oil. Data analysis techniques used the Two Factorial Anova test and Duncan's Test. Independent variables examined include cooking oil and wrapping methods with a hot temperature of 80 ° C, medium temperature of 45 ° C, and cold temperatures of 25 ° C with a packing time of 10 minutes. The results of the research in the Laboratory showed that the heavy metal content of Pb in fried foods wrapped in the highest black plastic with a hot temperature of 80 0C was an average of 0.881 ppm, while the lowest in the average control was 0.294 ppm in the treatment of used oil. In the new oil treatment, the highest metal content of Pb weight was 0.428 ppm, while the lowest in the control was 0.173 ppm. From the results of the Two Factorial Anova test that the interaction between oil and wrapping temperature there is an influence on Pb levels in fried foods with a significant value of <0.05, this means that there are interactions in all types of fried food treatment. Fried foods that experience Pb contamination cause food to not meet the requirements, this is because the wrapping process uses black plastic with different temperature treatments, where the more hot fried food is packaged, the more Pb content in fried foods, when food enters the body through blood flow will inhibit the cell's metabolic system, one of which is inhibiting Hb synthesis in the bone marrow which results in poor cognitive development, a weakened immune system accompanied by symptoms of autism and even death